Treatment of EBV driven lymphoproliferation with erythrophagocytosis: 12 year follow up. Issue 4 (1st April 2001) - Bethune, C A; Gompels, M M; Taylor, C; Angus, B; Spickett, G P
Abstract : This is a report of a case of Epstein-Barr virus (EBV) associated haemophagocytic syndrome in a 17 year old woman with antibody deficiency. For two years before this presentation, serology showed abnormally high titres to EBV early antigen, suggestive of persistent infection with EBV. She became acutely unwell with clinical features consistent with virus associated haemophagocytic syndrome (VAHS). Histology showed lymphoproliferation with erythrophagocytosis and evidence of EBV encoded RNAs in liver, spleen, and lymph node. VAHS is often fatal, particularly when it occurs in patients with underlying immunodeficiencies. In this case, treatment with intravenous immunoglobulin, aciclovir, and α interferon was followed by a dramatic recovery. Twelve years later the patient remains relatively well on regular intravenous immunoglobulin.